Artificial Intelligence-Based Mobile Health Solutions in the Health 4.0 Era - Ariefah Khairina Islahati; Purwono, Purwono; Bala Putra Dewa (Journal of Advanced Health Informatics Research, 2023)
In the Health 4.0 era, technological advances continue to bring major changes to the health care industry. Artificial intelligence (AI)-based Mobile Health (mHealth) solutions are an important innovation that will meet modern needs. As time goes by, modern society is increasingly dependent on health technology in everyday life, especially to manage their health conditions. The use of Mobile Health, especially via smartphone devices, has been proven to provide more personalized and affordable health services. Additionally, AI makes diagnosis and health monitoring easier. In this article, the concept of mHealth AI 4.0 is discussed, with particular emphasis on its critical role in providing responsive, proactive, and patient-focused healthcare. In the Health 4.0 era, it is hoped that we can make a positive contribution to improving the quality of health services by using this solution